2020
DOI: 10.1177/2280800020903630
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive injectable lumbar interbody fusion with mineralized collagen-modified PMMA bone cement: A new animal model

Abstract: This study was to develop a feasible and safe animal model for minimally invasive injectable lumbar interbody fusion using a novel biomaterial, mineralized collagen-polymethylmethacrylate bone cement (MC-PMMA), with unilateral pedicle screw fixation in an in vivo goat model. Eight goats ( Capra aegagrus hircus) were divided into three groups: MC-PMMA, unmodified commercial-polymethylmethacrylate bone cement (UC-PMMA), and a control group (titanium cage filled with autogenous bone, TC-AB). Each group of goats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Instead, PMMA bone cement may be encapsulated by fibrous tissue. Furthermore, the low attachment strength between the bone cement and surrounding bone [ 46 ] can cause slight movement of the cement [ 47 ], resulting in the formation of small particles or even dislodgment of the cement [ 48 ]. In contrast, bioactive bone cement has been shown to have excellent osseointegrative properties [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, PMMA bone cement may be encapsulated by fibrous tissue. Furthermore, the low attachment strength between the bone cement and surrounding bone [ 46 ] can cause slight movement of the cement [ 47 ], resulting in the formation of small particles or even dislodgment of the cement [ 48 ]. In contrast, bioactive bone cement has been shown to have excellent osseointegrative properties [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the circumferential contact index between MC-PMMA and bone was 36.4% higher, and histological staining revealed that the surface of MC-PMMA was in direct contact with new bone, while PMMA was encapsulated by fibrous tissue. Kong et al [ 100 ] developed a minimally invasive injectable lumbar interbody fusion goat model using MC-PMMA. The osteogenic potential of MC-PMMA, PMMA and titanium cage filled with autogenous bone (TC-AB) was compared at 3 and 6 months after surgery.…”
Section: Current Status Of MC and Its Application Of Related Absorbab...mentioning
confidence: 99%
“…It was found that PMMA bone cement showed a good osteogenic ability in a sheep model, but this finding needs to be verified in further clinical transformational experiments. Minimally invasive injectable lumbar interbody fusion with mineralized collagen–PMMA bone cement has far-reaching clinical value and shows potential application prospects ( Kong et al, 2020 ). However, not all allogeneic fillers are conducive to fusion.…”
Section: Post-processing Techniquesmentioning
confidence: 99%